Likelihood of Diagnosing Neuroblastoma in Isolated Horner Syndrome. Issue 3 (September 2019) - Ben Shabat, Avi; Ash, Shifra; Luckman, Judith; Toledano, Helen; Goldenberg-Cohen, Nitza
Abstract : Background: The need for an extensive evaluation for neuroblastoma in children with Horner syndrome is controversial. Methods: A retrospective study design was used. The cohort included 47 children with anisocoria who were diagnosed with Horner syndrome and 135 children with neuroblastoma evaluated at a pediatric medical center between 2007 and 2015. To detect neuroblastoma, patients with Horner syndrome underwent brain and cervical MRI, abdominal ultrasound, and/or measurement of urinary vanillylmandelic acid (VMA). The neuroblastoma group was evaluated for signs/symptoms of Horner syndrome at the time of diagnosis. Results: Seven patients with Horner syndrome were lost to follow-up, and the findings of the remaining 40 were categorized according to the age of the patient. Horner syndrome most frequently was idiopathic (58%), and in only 1 patient did the discovery of neuroblastoma precede the appearance of Horner syndrome. In the 21 patients aged 1–18 years, Horner syndrome was acquired in 15 patients and congenital in 6. The most common etiology was trauma (62%). Imaging was performed in 14 patients and VMA testing in 13. Neuroblastoma was diagnosed in 5 patients; in none was it related to Horner syndrome. In the 135 patients with neuroblastoma, most of the tumors were diagnosed at Stage 4 (60%) or Stage 3 (30%) with 53% originating in the abdomen. In one patient (0.74%) with signs/symptoms of Horner syndrome at diagnosis of neuroblastoma, the tumor had been identified prenatally and the diagnosis confirmed by imaging postnatally. Conclusions: The absence of occult neuroblastoma in children with Horner syndrome and of signs/symptoms of Horner syndrome in the children diagnosed with neuroblastoma suggests that Horner syndrome might not be as frequent a cause of neuroblastoma as previously thought. We recommend that full investigation for neuroblastoma be reserved for suspicious cases associated with additional systemic signs or symptoms.